2021
DOI: 10.1016/j.jbc.2021.100627
|View full text |Cite
|
Sign up to set email alerts
|

The Arabidopsis thaliana chloroplast division protein FtsZ1 counterbalances FtsZ2 filament stability in vitro

Abstract: Bacterial cell and chloroplast division are driven by a contractile “Z ring” composed of the tubulin-like cytoskeletal GTPase FtsZ. Unlike bacterial Z rings, which consist of a single FtsZ, the chloroplast Z ring in plants is composed of two FtsZ proteins, FtsZ1 and FtsZ2. Both are required for chloroplast division in vivo , but their biochemical relationship is poorly understood. We used GTPase assays, light scattering, transmission electron microscopy, and sedimentation assays to inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(37 citation statements)
references
References 91 publications
(208 reference statements)
2
35
0
Order By: Relevance
“…The single FtsZ present in bacteria must impart enough stability for protofilaments to support their scaffolding function within the Z ring while also allowing sufficient GTPase-dependent subunit turnover to drive protofilament and Z-ring dynamics ( 16 ). By contrast, we have shown that the A. thaliana chloroplast proteins AtFtsZ2 and AtFtsZ1, which coassemble, play distinct roles in promoting protofilament stability and dynamics, respectively ( 30 , 47 ). This suggests partial separation of these complementary functions during the evolution of chloroplasts from cyanobacteria.…”
Section: Resultsmentioning
confidence: 90%
See 3 more Smart Citations
“…The single FtsZ present in bacteria must impart enough stability for protofilaments to support their scaffolding function within the Z ring while also allowing sufficient GTPase-dependent subunit turnover to drive protofilament and Z-ring dynamics ( 16 ). By contrast, we have shown that the A. thaliana chloroplast proteins AtFtsZ2 and AtFtsZ1, which coassemble, play distinct roles in promoting protofilament stability and dynamics, respectively ( 30 , 47 ). This suggests partial separation of these complementary functions during the evolution of chloroplasts from cyanobacteria.…”
Section: Resultsmentioning
confidence: 90%
“…In vitro light scattering (LS) assays have shown that EcFtsZ typically undergoes rapid assembly upon addition of GTP, and rapid disassembly as GTP hydrolysis reduces protofilament stability ( 23 , 52 , 53 ). In contrast, we found that A. thaliana FtsZ2 (AtFtsZ2), one of the two FtsZs in A. thaliana chloroplasts ( 41 , 42 ), disassembled very slowly even after GTP was fully consumed, indicating AtFtsZ2 protofilaments are far more stable ( 47 ). Given the evolutionary relationship between cyanobacterial and chloroplast FtsZs ( 41 , 48 , 49 ), we were interested in the dynamic behavior of SeFtsZ and used LS assays ( 47 , 52 ) to investigate its assembly and disassembly dynamics.…”
Section: Resultsmentioning
confidence: 91%
See 2 more Smart Citations
“…In vitro , fast-growing bacterial FtsZ usually self-assembles into mostly single, dynamic protofilaments ( Chen et al, 2005 ; Chen and Erickson, 2005 ), but through lateral contact, FtsZ rearranges into bundles or sheets in the solution of calcium, high concentration magnesium, or in some crowding environments ( Yu and Margolin, 1997 ; Mukherjee and Lutkenhaus, 1999 ; Chen and Erickson, 2009 ). Some slow-growing bacterial and chloroplast FtsZ could assemble into bundles, and circles directly ( White et al, 2000 ; Chen et al, 2007 , 2017b ; Wang et al, 2019 ; Porter et al, 2021 ). FtsZ filaments are also regulated by some associated proteins.…”
Section: Introductionmentioning
confidence: 99%